One new genus and three new species of the Penenirmus-complex (Phthiraptera: Ischnocera) from China, with resurrection of Picophilopterus Ansari, 1947 - Gustafsson, Daniel R.; Adam, Costică; Zou, Fasheng (Zootaxa, 2022)
Three new species of chewing lice of the Penenirmus-complex (Phthiraptera: Ischnocera) are described and illustrated from woodpeckers (Picidae) and barbets (Megalaimidae) occurring in China. They are: Picophilopterus blythipici new species from Blythipicus pyrrhotis sinensis (Rickett, 1897), Laimoloima ruiliensis new genus, new species from Psilopogon asiaticus asiaticus (Latham, 1790), and Laimoloima tandani new genus, new species from Psilopogon virens virens (Boddaert, 1783). In addition, we provide illustrations of Picophilopterus pici sensu lato ex Picus canus sordidior (Rippon, 1906), and we present evidence that justifies resurrecting the genus Picophilopterus Ansari, 1947 to include the species infesting woodpeckers and Neotropical barbets (Capitonidae). Also, we erect the new genus Laimoloima to include the species from Asian barbets (Megalaimidae). The taxonomic position of Penenirmus species from African barbets (Lybiidae) and honeyguides (Indicatoridae) is unresolved. An updated checklist of the species in the Penenirmus-complex parasitic on non-passeriform hosts is provided, including species of the genus Turnicola Clay & Meinertzhagen, 1938.